Robust synchronization of master-slave chaotic systems using approximate model: An experimental study. (February 2018) - Ahmed, Hafiz; Salgado, Ivan; Ríos, Héctor
Abstract: Robust synchronization of master slave chaotic systems are considered in this work. First an approximate model of the error system is obtained using the ultra-local model concept. Then a Continuous Singular Terminal Sliding-Mode (CSTSM) Controller is designed for the purpose of synchronization. The proposed approach is output feedback-based and uses fixed-time higher order sliding-mode (HOSM) differentiator for state estimation. Numerical simulation and experimental results are given to show the effectiveness of the proposed technique. Graphical abstract: Highlights: Approximate model based master-slave synchronization of chaotic systems. The model is obtained by approximating the system dynamics. Uniform Robust Exact Differentiator based sate estimation. Continuous Singular Terminal Sliding Mode (CSTSM) control based synchronization. Experimental results validate the theoretical findings.